Knowledge, Attitude and Practice of Self-Medication among Nursing Students of Nepalgunj Nursing Campus Kohalpur Banke - Dhami, Dabal Bahadur; Dhakal, Sanjeeva (Journal of Nepalgunj Medical College, 2020)
Introduction: Self-medication is widely practiced among the nursing students because of easy availability and accessibility of the drugs. Inappropriate self-medication can leads to increased resistance among pathogens, wastage of resources, can cause serious harm and increase morbidity; which indicates needs of responsible self-medication. Aims: This study was to assess the self-medication knowledge, attitude and practice among nursing students. Methods: This was a questionnaire based descriptive cross sectional study conducted in Nursing students of Nepalgunj Nursing Campus, Kohalpur, on August 2019. Questions related to various aspects of self-medication was used for data collection. Results: Out of 120 students, 102 (85%) students were found practicing self-medication with reason of no need to visit the doctor for minor illness 78%, for quick relief 75% and for time saving 50%. Only 15% not taken self-medication reasoning there was risk of adverse effects 65% and risk of using wrong drugs 60%. The source of information of the drugs used for self-medication was previous prescription and text book was 50% and 35% respectively and the source of the drugs was medical store, 88.2%. Majority of 96% took for headache followed by fever 83.3%; menstrual symptoms 68.6%; and cough and cold 68.6% and dirrhoea 64.7%. Most of the students 96% took analgesics and antipyretics drugs. Conclusion: Our study shows that self-medication is significantly practiced by nursing students. There is need to aware them about advantages and disadvantages of self-medication in order to ensure safety and proper use of drugs.